Strong pinning and vortex energy distributions in single-crystalline Ba(Fe1_xCox)2As2 - Demirdis, S. (2011)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina